2010
DOI: 10.1179/016164109x12537002794048
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect ofAngelicae Tenuissimae Radixon expressions of cyclooxygenase-2 and inducible nitric oxide synthase in mouse BV2 microglial cells

Abstract: The present study indicates that Angelicae Tenuissimae Radix can be applied as a valuable treatment for brain inflammation and headache.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…However, the high concentrations of NO induced by certain pathological conditions, such as brain ischemia, inflammation, neurodegenerative diseases, and may result in neuronal dysfunction (Heales et al, 1999; Murphy, 1999; Lee et al, 2010). NO also causes apoptotic neuronal cell death (Lee et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, the high concentrations of NO induced by certain pathological conditions, such as brain ischemia, inflammation, neurodegenerative diseases, and may result in neuronal dysfunction (Heales et al, 1999; Murphy, 1999; Lee et al, 2010). NO also causes apoptotic neuronal cell death (Lee et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…tenuissima ) is one of the traditional Asian medicines that has been used to treat headaches, diarrhea, epilepsy, rheumatic arthritis, and gynecological diseases and anemia for women [ 9 ]. Recently, it has been demonstrated to have various anti-viral, anti-osteoporosis, and anti-inflammatory effects [ 10 , 11 , 12 ]. In our previous study, it was confirmed that fermented A. tenuissima root (FAT) had an anti-melanogenetic effect, and we found that the content of ligustilide, and one of the active compounds, was higher during fermentation by Aspergillus oryzae [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Angelica tenuissima Nakai (Umbelliferae family) has been used in traditional Asian medicines to treat headaches and in remedies for women with gynecological diseases and anemia [3]. Recently, the interferon-mediated antiviral [4], anti-osteoporosis [5], and anti-inflammatory activities [6] of A. tenuissima Nakai have been identified. However, the cosmetic uses of the crude extract of the A. tenuissima (AT) root and its fermented product (FAT) as a skin-whitening agent have not been investigated.…”
Section: Introductionmentioning
confidence: 99%